Predictors of University Student Satisfaction with Life, Academic Self-Efficacy, and Achievement in the First Year - Wilcox, Gabrielle; Nordstokke, David (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2019)
Understanding personal factors that contribute to university student satisfaction with life is important in order to determine how we can better prepare students for the transition to post-secondary education and support them during this transition. This study examined predictors of university student satisfaction with life, academic self-efficacy, and self-reported academic achievement in their first year of university. First-year students (n = 66) completed selfreport measures of academic achievement, university well-being, satisfaction with life, personality, and mental health. A linear regression analysis approach was applied to the data. Results indicated that academic satisfaction and school connectedness predicted satisfaction with life but that academic self-efficacy and college gratitude did not, conscientiousness predicted academic self-efficacy, college well-being predicted self-reported achievement, and anxiety predicted achievement but depression did not. This study highlights the importance of understanding the personal factors that influence well-being and achievement during the transition to university.